Social Media Application as a New Paradigm for Business Communication Strategies: The Role of Knowledge, Attitude, and Practices (KAP) - Adriyanto, Andhy Tri; Tukinah, Ukie; Hartarini, Yovita Mumpuni (Jurnal Dinamika Manajemen, 2025)
Business communication methods have had a significant impact on both private and public enterprises. The company’s communication strategy has emerged as the most crucial problem, affecting all firms. This study seeks to investigate the link between company communication strategy knowledge, attitudes regarding social media usage, and social media use habits. This study looks at how attitudes regarding social media use influence the link between company communication strategy knowledge and social media use habits. To acquire the sample, thesurvey employed a non-probability convenience sampling technique, recruiting willing respondents who gave their agreement for data collection. The research collected comments from 250 people. The findings supported the link between company communication strategy expertise and attitudes toward social media use. Similarly, the findings of this study supported the beneficial association between attitudes about social media use and practices. Attitudesabout social media usage mediated the link between understanding company communication strategies and social media use behaviors. This study presents a systematic and comprehensive research strategy for investigating the outcomes of company communication initiatives. The generalizability of these findings suggests promising paths for future study on company communication methods.